Maillard reaction products from Tilapia (Oreochromis mossambicus) scale collagen peptides conjugated with Galactooligosaccharides of different purities: Characterization, antioxidant activity, and impact on the growth of probiotics - Zhanhui Liu; Bing Chen; Songlei Wang; Zhengyuan Xiao; Hongxing Guo; Zhengguang Wang; Xinyuan Qi; Shiyuan Dong; Zifang Zhao (Food Chemistry: X, 2025)
This study investigated the effects of galactooligosaccharide (GOS) purity (80 % and 95 %) and heating time (60 and 150 min) on characterization and bioactivities of Maillard reaction products (MRPs) formed by conjugating tilapia scale collagen peptides with GOS at 90 °C. Spectral analyses, degree of grafting, and furosine content showed that lower-purity GOS exhibited higher glycation reactivity. Amino acid composition and advanced glycation end products analyses showed that arginine was the primary amino acid involved in glycation, with abundant formation of methylglyoxal-derived hydroimidazolone 1 (MG-H1). Digested MRPs maintained strong antioxidant activity, particularly in the lower-purity GOS group. Meanwhile, MRPs heated for 150 min enhanced L. casei, L. pentosus, and B. bifidum growth, while those heated for 60 min favored B. longum. MG-H1 level was positively correlated with antioxidant activity and B. bifidum growth (p < 0.01). This study highlights the broad application potential of glycated bioactive peptides with lower-purity GOS.